36.4k views
3 votes
What is the value of c in the equation 2(x-3)+9=3(x+1)+x

2 Answers

6 votes

Answer:

I am not sure if you mean x or c, but x would be equal to 0

Explanation:

Step 1: Simplify both sides of the equation.

2 (x - 3) + 9 = 3 (x + 1) + x

(2) (x) + (2) (- 3) + 9 = (3) (x) + (3) (1) + x

2x + - 6 + 9 = 3x + 3 + x

(2x) + (- 6 + 9) = (3x + x) + (3)

2x + 3 = 4x + 3

Step 2: Subtract 4x from both sides.

2x + 3 - 4x = 4x + 3 - 4x

- 2x + 3 = 3

Step 3: Subtract 3 from both sides.

- 2x + 3 - 3 = 3 - 3

- 2x = 0

Step 4: Divide both sides by - 2.

- 2x/- 2 = 0/- 2

x = 0

User Rafael Xavier
by
5.3k points
5 votes

Answer:

x = 0 (I must assume you had a typo since c is not a variable in this equation!

Explanation:

Solve for x:

2 (x - 3) + 9 = 3 (x + 1) + x

2 (x - 3) = 2 x - 6:

2 x - 6 + 9 = 3 (x + 1) + x

Grouping like terms, 2 x - 6 + 9 = 2 x + (-6 + 9):

2 x + (-6 + 9) = 3 (x + 1) + x

9 - 6 = 3:

2 x + 3 = 3 (x + 1) + x

3 (x + 1) = 3 x + 3:

2 x + 3 = 3 x + 3 + x

Grouping like terms, 3 x + x + 3 = (3 x + x) + 3:

2 x + 3 = (3 x + x) + 3

3 x + x = 4 x:

2 x + 3 = 4 x + 3

Subtract 4 x from both sides:

(2 x - 4 x) + 3 = (4 x - 4 x) + 3

2 x - 4 x = -2 x:

-2 x + 3 = (4 x - 4 x) + 3

4 x - 4 x = 0:

3 - 2 x = 3

Subtract 3 from both sides:

(3 - 3) - 2 x = 3 - 3

3 - 3 = 0:

-2 x = 3 - 3

3 - 3 = 0:

-2 x = 0

Divide both sides of -2 x = 0 by -2:

(-2 x)/(-2) = 0/(-2)

(-2)/(-2) = 1:

x = 0/(-2)

0/(-2) = 0:

Answer: x = 0

User Debie
by
5.4k points